Dietary knowledge, attitude, practice, and associated factors among pregnant mothers in Ethiopia: a systematic review and meta-analysis - Bayked, Ewunetie Mekashaw; Yimer, Ebrahim M.; Gelaw, Tiruset; Mohammed, Abdu Seid; Mekonen, Nigusie Abebaw (Frontiers in Public Health, 2024)
Background Despite global efforts, progress in reducing maternal malnutrition falls short of international goals, which is the same for Ethiopia, provided that studying dietary knowledge, attitude, and practice and their determinants is crucial to developing and implementing effective interventions, which this review tried to investigate in an Ethiopian context. Methods We searched on Scopus, HINARI, PubMed, and Google Scholar on January 3, 2024. We used the Joanna Briggs Institute’s (JBI’s) tools and the “preferred reporting items for systematic reviews and meta-analyses (PRISMA) 2020 statement” to evaluate bias and frame the review, respectively. The data were analyzed using Stata 17. Certainty was assessed using sensitivity and subgroup analyses and the Luis Furuya-Kanamori (LFK) index. The random effects model was used to determine the effect estimates with a p value less than 0.05 and a 95% CI. Results The pooled good dietary knowledge, favorable attitude, and good practice were 48.0% (95% CI: 39.0–57.0%), 47.0% (95% CI: 38.0–55.0%), and 34.0% (95% CI: 28.0–40.0%), respectively. Knowledge and attitude had bidirectional relationships and were affected by sociodemographic variables and gynecological issues. The dietary practice was influenced by urban residency (OR = 6.68, 95% CI: 2.49–10.87), food security (OR = 3.51, 95% CI: 1.02–5.99), knowledge (OR = 4.53, 95% CI: 3.22–5.74), nutrition information (OR = 3.07, 95% CI: 1.13–5.02), attitude (OR = 2.32, 95% CI: 1.34–3.30), family support (OR = 2.14, 95% CI: 1.43–2.85), perceived severity of malnutrition (OR = 2.07, 95% CI: 1.82–2.31), and positive perception of dietary benefit (OR = 2.19, 95% CI: 1.56–2.82). Conclusion The good dietary practice was lower than the knowledge and the favorable attitude toward it. It was influenced by sociodemographic variables, income and wealth, knowledge and information, attitudes and intentions, gynecological and illness experiences, family support and decision-making, and expectations of nutrition outcomes and habits. Sociodemographic and gynecological issues were also found to influence both dietary knowledge and attitude, which were also found to have bidirectional relationships. Systematic review registration: PROSPERO identifier: CRD42023440688.